(untitled) (Journal of Science and Technology, 2016)
Terminalia catappa is a common tree found in Ghana but it is much underutilized. The objective was therefore set to investigate the medicinal and nutritive potential of two common varieties of the plant; the red and yellow varieties. The proximate composition of the nut and pulp of the two varieties were determined using certified methods of the Association of Official Analytical Chemists. Phytochemical screening was also determined using standard screening methods. The red nut had a moisture content of 31.05%; crude fat, 36.9%; protein, 22.19%; ash, 2.76%; carbohydrate, 5.24% and crude fibre, 1.86%. The pulp contained up to 81.96% moisture; 0.04% crude fat; 1.07% protein; 1.47% ash; 14.05% carbohydrates and 1.41% crude fibre. The moisture content constituted 32.06% of the nut of the yellow variety, crude fat was 35.69%; protein, 23.05%; ash, 2.68%; carbohydrate, 4.92% and crude fibre, 1.6%. The pulp of the yellow variety had the proximate composition as: moisture, 84.37%; crude fat, 0.05%; crude protein, 1.54%; ash, 1.62%; carbohydrate, 11.03%; crude fibre, 1.39%. The pulps of both varieties were found to contain saponins, general glycosides, flavonoids, alkaloids, anthraquinones and anthraquinone glycosides. The nut of the yellow variety had terpenoids and steroids present in it while the nut of the red variety had alkaloids present. Statistical analyses carried out showed that there were no significant differences (p≤0.05) between the two varieties based on their proximate composition.